(untitled) - McConnell, Campbell R. (Boston, 2008)
McConnell and Brue’s Macroeconomics: Principles, Problems, and Policies is the leading Principles of Macroeconomics textbook because it is innovative and teaches students in a clear, unbiased way. The 17th Edition builds upon the tradition of leadership by sticking to 3 main goals: help the beginning student master the principles essential for understanding the economizing problem, specific economic issues, and the policy alternatives; help the student understand and apply the economic perspective and reason accurately and objectively about economic matters; and promote a lasting student interest in economics and the economy.
Keywords: Macroeconomics,Kinh tế học vĩ mô